2005
DOI: 10.1128/mcb.25.18.8239-8250.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pathway- and Expression Level-Dependent Effects of Oncogenic N-Ras: p27Kip1 Mislocalization by the Ral-GEF Pathway and Erk-Mediated Interference with Smad Signaling

Abstract: Overactivation of Ras pathways contributes to oncogenesis and metastasis of epithelial cells in several ways, including interference with cell cycle regulation via the CDK inhibitor p27Kip1 (p27) and disruption of transforming growth factor ␤ (TGF-␤) anti-proliferative activity. Here, we show that at high expression levels, constitutively active N-Ras induces cytoplasmic mislocalization of murine and human p27 via the Ral-GEF pathway and disrupts TGF-␤-mediated Smad nuclear translocation by activation of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 78 publications
(161 reference statements)
1
47
0
Order By: Relevance
“…To date, activation of the Ras and Akt/PKB signaling pathways, which are commonly deregulated in human neoplasms, have been found to induce the cytoplasmic localization of p27 by inducing its phosphorylation on distinct residues (Liu et al 2000;Kouvaraki et al 2002;Liang et al 2002;Kfir et al 2005;Besson et al 2006). We found that significant amounts of p27 CK − localized in the cytoplasm in the lung epithelium, luteal cells, and primary fibroblasts, as well as in lung tumors.…”
Section: Discussionmentioning
confidence: 63%
“…To date, activation of the Ras and Akt/PKB signaling pathways, which are commonly deregulated in human neoplasms, have been found to induce the cytoplasmic localization of p27 by inducing its phosphorylation on distinct residues (Liu et al 2000;Kouvaraki et al 2002;Liang et al 2002;Kfir et al 2005;Besson et al 2006). We found that significant amounts of p27 CK − localized in the cytoplasm in the lung epithelium, luteal cells, and primary fibroblasts, as well as in lung tumors.…”
Section: Discussionmentioning
confidence: 63%
“…In fact, p27 expression is usually maintained in these tumors but the protein is partially relocated to the cytoplasm of tumor cells (Besson et al, 2006;Kelly-Spratt et al, 2009). Ras activation is known to cause cytoplasmic translocation of p27, including in lung tumors, notably via the downstream activation of the Ral and phosphatidylinositol-3 kinase pathways (Liu et al, 2000;Kfir et al, 2005;Besson et al, 2006;Kelly-Spratt et al, 2009). Monitoring of p27 protein levels in urethane-induced lung tumors confirmed the maintenance of both WT p27 and p27…”
Section: P27mentioning
confidence: 78%
“…Ras activation indirectly causes cytoplasmic localization of p27 via the activation of its effectors Ral-GEF/Ral and phosphatidylinositol-3 kinase/Akt and Raf1/MEK/ERK pathways (Liu et al, 2000;Kfir et al, 2005;Besson et al, 2006). Phosphorylation of p27 on three different sites has been shown to result in cytoplasmic localization: phosphorylation on Ser10 by Akt, ERK2, CDK5 or hKIS promotes CRM1-mediated nuclear export; whereas phosphorylation on Thr157 by Akt, SGK1 or Pim, or on Thr198 by Akt, RSK1, Pim, or LKB1/ AMPK were shown to result in cytoplasmic retention of the protein via binding with 14-3-3 proteins and also for Thr157 by inactivating the nuclear localization sequence of p27 (Boehm et al, 2002;Ishida et al, 2002;Liang et al, 2002;Fujita et al, 2002Fujita et al, , 2003Shin et al, 2005;Kawauchi et al, 2006;Chu et al, 2008;Hong et al, 2008;Morishita et al, 2008;Short et al, 2008;Larrea et al, 2009).…”
Section: P27mentioning
confidence: 99%
“…66 Interestingly, oncogenic N-Ras has been shown to induce cytoplasmic localization of p27 via the Ral-GEF pathway, with activation of Mek/Erk, thereby disrupting Smad2/3 nuclear localization and TGFβ-mediated growth inhibition. 82 Nevertheless, the data suggest that TGFβ signaling utilizes p27 for growth inhibition by inhibiting Cdk2 activity. Specifically, we show that there is increased nuclear p27 and decreased Cdk2 kinase activity in HEC-1A cells at the same time growth inhibition is achieved following TGFβ treatment.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%